Unsheltered homeless and unstably housed adults have higher levels of stress and more health risk factors than sheltered homeless adults. Issue 1 (2nd January 2023) - Ra, Chaelin K.; Hébert, Emily T.; Alexander, Adam; Kendzor, Darla E.; Suchting, Robert; Businelle, Michael S.
ABSTRACT: In the United States, approximately 580, 000 individuals were homeless on a single night in 2020. Homelessness can be categorized into three subgroups: sheltered homeless, unsheltered homeless, and unstably housed. This study aimed to empirically examine whether homelessness subgroups were related to current stress, recent utilization of shelter-based mental health services, and current health risk factors. Data were collected at multiple homeless shelters in 2016 in the Oklahoma City area ( N = 575). All participants completed assessments of demographic characteristics, including age, sex, race, marital status, years of education, and incarceration history and victimization. Multiple linear and logistic regression analyses were conducted. Results indicated that the sheltered group was younger and more likely to be White than the unsheltered group, had higher levels of education, and reported more lifetime months in jail than the unstably housed group. Unsheltered homeless and unstably housed adults used fewer shelter-based health services, exhibited more health risk factors, experienced greater levels of stress, and had higher levels of food insecurity than sheltered homeless adults. Homeless adults who reside at shelters benefit most from available shelter services. The development of policies and programs targeted toward increasing sheltering options for unsheltered and unstably housed adults is needed.